Personality disorders in individuals with functional seizures: a systematic review - Sammarra, Ilaria; Martino, Iolanda; Marino, Laura; Fortunato, Francesco; Gambardella, Antonio (Frontiers in Psychiatry, 2024)
Functional seizures (FS) are classified as a conversion disorder in the DSM-5 and as a dissociative disorder in the ICD-11, showing a multifactorial psychopathology with several psychiatric comorbidities, such as depression and anxiety. Several studies found a correlation between FS and personality disorders, mainly belonging at Cluster B. Within this last group, borderline personality disorder (BPD) or borderline personality traits are the higher prevalent types in FS. Indeed, emotion dysregulation is a hallmark in BPD and commonly reported in subjects with FS. Cluster C personality disorders, such as avoidant or obsessive-compulsive, have been also reported in FS. In this review, we aim to evaluate the relationship between FS and personality disorders. Assessment of personality disorder in a context of FS is relevant for the most appropriate intervention. Cognitivebehavioral therapy (CBT) is considered as the first-line approach to treat FS. Among the various CBT strategies, dialectical-behavior therapy, targeting specifically emotion dysregulation, could be helpful in a setting of BPD. Future research should assess the advantages of a systematic evaluation of personality disorders in FS, to address the specific treatment planning, evaluating its effectiveness on seizure recurrency, psychological comorbidities and quality of life. * * * * ** **